2015
DOI: 10.1007/s00330-015-3946-2
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion- and pattern-based quantitative CT indexes using contrast-enhanced dual-energy computed tomography in diffuse interstitial lung disease: relationships with physiologic impairment and prediction of prognosis

Abstract: • Dual-energy CT (DECT) produces morphologic and parenchymal enhancement information. • Automated lung segmentation enables analysis of disease extent and severity. • This prospective study showed value of DECT in DILD patients. • Parameters on DECT enable characterization and survival prediction of DILD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…FVC (mean 75.74) has mild reduction indicating restrictive lung diseases, which agrees with Moon et al and Jacob et al, with FVC mean 76.5 ± 18.2, 71% respectively [3,31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…FVC (mean 75.74) has mild reduction indicating restrictive lung diseases, which agrees with Moon et al and Jacob et al, with FVC mean 76.5 ± 18.2, 71% respectively [3,31].…”
Section: Discussionsupporting
confidence: 89%
“…Normal lung was significantly correlated with FVC% (r = 0.455, p value = 0.011), FEV1% (r = 0.691, p value = < 0.001), FEV1/FVC% (r = 0.753, p value = < 0.001) that is matching with Moon's study which showed a very strong positive correlation with functional lung volume and FVC% (r = 0.72, p < 0.01) [31]. Shin et al's study also agreed with our study, which showed a high positive correlation with FLV and a high positive correlation with FVC and FEV1 (r = 0.80 and 0.73, p < 0.01) [21].…”
Section: Discussionsupporting
confidence: 86%
“…ILAs were defined as particular patterns of increased lung density, including ground-glass or reticular abnormalities, diffuse centrilobular nodularity, nonemphysematous cysts, and honeycombing or traction bronchiectasis, affecting more than 5% of any lung zone [21]. ILAs were assessed subjectively by adding and scoring the overall extent of fibrosis-related lung parenchymal abnormalities, which were estimated from the nearest 5% of parenchymal involvement to the whole lung volume (100%) [22,23]. We used an in-house computer software to assess and automatically calculate the emphysema index, which was defined as the volume fraction of the lung below − 950 HU [23,24].…”
Section: Ct Findingsmentioning
confidence: 99%
“…Comparison studies on the assessment of pulmonary perfusion using DECT have shown good agreement with both planar scintigraphy and SPECT/CT . The DECT approach was also successful to detect perfusion defects in the context of pulmonary embolism and parenchymal lung disease . Other single‐energy CT (SECT) techniques may also process contrast‐enhanced CT images to produce functional maps of the lung parenchyma; however, they do not quantitatively address the perfused blood volume.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The DECT approach was also successful to detect perfusion defects in the context of pulmonary embolism [18][19][20][21][22] and parenchymal lung disease. 23,24 Other single-energy CT (SECT) techniques may also process contrast-enhanced CT images to produce functional maps of the lung parenchyma; 6,25,26 however, they do not quantitatively address the perfused blood volume.…”
Section: Introductionmentioning
confidence: 99%